Application of gel electrolyte in rechargeable magnesium battery
By using gel electrolytes prepared by using magnesium salts, ring-open polymer monomers and initiators in rechargeable magnesium batteries, the safety hazards and insufficient performance problems of liquid electrolytes are solved, and efficient magnesium deposition-dissolution and battery stability are achieved. .
Patent Information
- Application Number
- CN202411298151.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The liquid electrolytes of existing rechargeable magnesium batteries have safety risks such as side reaction risks, leakage, volatility and flammability, and the oxidation stability and magnesium deposition and dissolution efficiency are insufficient, which affects the stability and performance of the battery.
Gel electrolytes based on magnesium salts, ring-opening polymerized monomers, solvents and initiators are used, specifically including dibenzylamine magnesium chloride lithium chloride complex, and ring-opening polymerized monomers are 1,3-dioxolane ring , the solvent is tetrahydrofuran and the initiator is scandium trifluoromethanesulfonate. The gel electrolyte is prepared by ring-opening polymerization to increase the compatibility and oxidation stability of the magnesium negative electrode.
It significantly improves the magnesium deposition-dissolution efficiency, reduces the possibility of side reactions, enhances the safety and mechanical stability of the battery, improves the electrochemical performance, reduces the overpotential, and achieves high capacity retention and Coulomb efficiency.
Smart Images

Figure CN119324250A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnesium batteries, and in particular relates to application of a gel electrolyte in a rechargeable magnesium battery. Background Art
[0002] Magnesium is located diagonally opposite lithium in the periodic table, with similar ionic radii and chemical properties. 2+ As a divalent ion, Mg has a high theoretical capacity (3833 mAh cm –3 ); In addition, magnesium is abundant in nature, has low cost, and has the potential for sustainable development. Magnesium has advantages such as stability in air and rarely produces dendrites, which makes it have good safety characteristics. Therefore, rechargeable magnesium batteries have become a strong competitor for the next generation of energy storage systems. The electrolyte is a key factor affecting the development of rechargeable magnesium batteries. The development of an electrolyte system with strong oxidation stability, high conductivity, high magnesium reversible deposition-dissolution efficiency, excellent cycle performance and low cost is crucial to promote the development of high-performance rechargeable magnesium batteries.
[0003] The feasibility of rechargeable magnesium batteries was first proposed by Gregory et al. in 1990 (Gregory TD, Hoffman RJ, Winterton, Development of an ambient secondary magnesium battery, J. Electrochem. Soc., 1990, 137: 775-780). In 2000, Aurbach et al. achieved a major breakthrough in the field of rechargeable magnesium batteries (Aurbach D, Lu Z, Schechter A, et al. Prototype systems for rechargeable magnesium batteries. Nature, 2000, 407: 724-727). Subsequently, a large number of researchers have devoted themselves to the research of rechargeable magnesium battery electrolytes and made significant progress.
[0004] First, magnesium salts based on Grignard reagents are widely used due to their highly reversible magnesium deposition-stripping properties. However, due to disadvantages such as low oxidation stability, high corrosiveness, and nucleophilicity, Grignard reagents have gradually lost favor. In order to further enhance the oxidation stability window and the reversibility of magnesium deposition-stripping, electrolytes based on bis(hexamethyldisilazide) magnesium, magnesium borohydride, and mixed salts containing halides (such as magnesium aluminum chloride complexes and magnesium lithium chloride complexes) have been gradually developed, and their oxidation stability can reach 3V vs.Mg / Mg 2+ The magnesium deposition-stripping efficiency is as high as 99%, and their non-nucleophilicity broadens the cathode compatibility.
[0005] Secondly, the development of magnesium salts with bulky weakly coordinated anions, such as magnesium tetrakis(hexafluoroisopropyl)borate and magnesium carborane cluster salts, further expanded the oxidative stability of the electrolyte (>4 V vs.Mg / Mg 2+ ). Their properties, including highly reversible magnesium deposition-stripping efficiency, non-corrosiveness, and broad cathode compatibility, have greatly promoted the development of liquid electrolytes for rechargeable magnesium batteries.
[0006] Thirdly, the incorporation of beneficial additives has been shown to change the solvation structure of the electrolyte, making it possible to utilize passivating salts in rechargeable magnesium batteries. For example, magnesium bis(trifluoromethanesulfonyl imide) can be used with magnesium chloride or ionic liquids to alleviate the passivation of the metallic magnesium anode.
[0007] In addition, by introducing a chelating agent, the overpotential of magnesium bis(trifluoromethanesulfonylimide) and magnesium trifluoromethanesulfonate electrolytes is greatly reduced, so that the reversibility of magnesium deposition-dissolution is significantly enhanced.
[0008] Although important progress has been made in liquid electrolytes for rechargeable magnesium batteries, their inherent shortcomings remain worrisome. Soluble impurities present in liquid electrolytes increase the possibility of side reactions, thereby compromising the stability of the positive and negative electrodes, ultimately leading to the deterioration of the electrochemical performance of the battery. In addition, liquid electrolytes also have risks such as leakage, volatilization and flammability, which will pose serious safety hazards in practical applications. In order to address these challenges, gel polymer electrolytes have been proposed as a means to improve the overall performance of batteries. By dispersing magnesium salts in a flexible polymer matrix, this electrolyte has significant advantages, including higher thermal and mechanical stability, excellent structural flexibility, higher safety, wider operating temperature range, and less tendency to side reactions. In addition, in-situ gel electrolytes also exhibit good interfacial contact, high room temperature ionic conductivity, low interfacial impedance, and excellent compatibility between the positive and negative electrodes. Based on the improvement of these comprehensive properties, gel polymer electrolytes are expected to become a promising direction in future practical applications. Summary of the invention
[0009] To achieve the above-mentioned purpose, the present invention provides an application of a gel electrolyte in a rechargeable magnesium battery, wherein the gel electrolyte comprises a magnesium salt, a ring-opening polymerization monomer, a solvent and an initiator, wherein the ring-opening polymerization monomer is 1,3-dioxolane. Generally speaking, the 1,3-dioxolane monomer has good compatibility with lithium metal, but has a passivation effect on the metal magnesium negative electrode, and the passivation effect on the metal magnesium will be weakened by ring-opening polymerization of the monomer. At the same time, the magnesium salt contains chloride, which can further alleviate the passivation phenomenon of the magnesium negative electrode, thereby improving the compatibility of the gel electrolyte with the magnesium negative electrode.
[0010] In some embodiments, the magnesium salt is dibenzylamine magnesium chloride lithium chloride complex or other magnesium chloride lithium chloride complex.
[0011] In some embodiments, the solvent is tetrahydrofuran.
[0012] In some embodiments, the initiator is scandium trifluoromethanesulfonate. Preferably, the mass fraction of the initiator relative to 1,3-dioxolane is 3-4 wt %.
[0013] In some embodiments, a magnesium salt is dissolved in a tetrahydrofuran solvent to form a magnesium salt / tetrahydrofuran electrolyte, and the magnesium ion concentration in the magnesium salt / tetrahydrofuran is 0.5 mol / L.
[0014] In some embodiments, the volume ratio of the magnesium salt / tetrahydrofuran electrolyte to the ring-opening polymerization monomer is controllable. Preferably, the volume ratio of the magnesium salt / tetrahydrofuran electrolyte to the ring-opening polymerization monomer is 3:1.
[0015] In some embodiments, aluminum chloride can be first added to the magnesium salt / tetrahydrofuran electrolyte and fully reacted for 24 hours to improve the activity and oxidation stability of the electrolyte. The amount of aluminum chloride used is 1 to 2 times the concentration of magnesium ions, that is, the molar ratio of aluminum ions to magnesium ions is 1:1 to 2:1.
[0016] In some embodiments, the gel electrolyte is prepared by the following method:
[0017] Step 1), adding an initiator to a ring-opening polymerization monomer, and mixing at 40° C. for 8-9 minutes to obtain a solution A;
[0018] Step 2), adding the magnesium salt / tetrahydrofuran electrolyte to the solution A, and vigorously stirring at room temperature (stirring speed is about 1000r / min) until a homogeneous solution is obtained to obtain a precursor solution B;
[0019] Step 3), leaving the precursor solution B at room temperature for more than 24 hours to obtain a transparent gel electrolyte.
[0020] In a preferred embodiment, the above operations are all carried out in a glove box filled with argon atmosphere (water content <0.01 ppm, oxygen content <0.01 ppm).
[0021] In some embodiments, the rechargeable magnesium battery is prepared by the following method:
[0022] A 2032 type 316 stainless steel battery shell, metal magnesium, and deintercalation type Mo6S8 were used as the positive electrode, the precursor solution B was added, metal magnesium was used as the negative electrode, and a polyethylene film was used as a separator to assemble a button battery, which was left to stand for more than 24 hours.
[0023] In some embodiments, the rechargeable magnesium battery (full battery) is cycled 600 times at room temperature, and the average discharge specific capacity is 95.6 mAh / g at a rate of 0.5C. After 600 charge and discharge cycles, the discharge specific capacity remains above 92 mAh / g, the capacity retention rate reaches above 88%, and the coulombic efficiency remains at 100%.
[0024] The rechargeable magnesium battery gel polymer electrolyte of the present invention uses 0.5 mol / L dibenzylamine magnesium chloride lithium chloride complex or other lithium chloride magnesium chloride complex as the active magnesium salt, and the in-situ formed gel electrolyte has good magnesium negative electrode compatibility through Lewis acid-induced 1,3-dioxolane ring-opening polymerization, and the magnesium deposition-dissolution efficiency after stabilization reaches 98%, and the overpotential is less than 100mV. The anodic oxidation decomposition potential of the gel electrolyte on stainless steel can reach 2.5V vs.Mg / Mg 2+ The gel polymer electrolyte prepared by in-situ ring-opening polymerization has the advantages of simple preparation process, cheap raw materials, excellent electrochemical performance, structural flexibility and good mechanical stability.
[0025] Technical Effects
[0026] The rechargeable magnesium battery gel polymer electrolyte proposed by the present invention has the advantages of high magnesium deposition-dissolution efficiency, low overpotential, good positive electrode matching, high safety and flexibility. The possibility of side reactions is reduced, thereby improving the stability of the positive and negative electrodes, and ultimately promoting a significant improvement in the electrochemical performance of the entire battery; the electrolyte has almost no risk of leakage, volatilization, etc., and will not cause serious safety hazards in practical applications. The obtained rechargeable magnesium battery has excellent performance and provides a feasible way for the practical application of solid-state rechargeable magnesium batteries.
[0027] The present invention discloses the application of a simple ring-opening polymerization gel electrolyte in a rechargeable magnesium battery. The magnesium salt in the electrolyte is a commercially available dibenzylamine magnesium chloride lithium chloride complex or other magnesium chloride lithium chloride complex. The solvent is tetrahydrofuran with a concentration of 0.5 mol / L. The monomer of the ring-opening polymerization is 1,3-dioxolane, and the initiator is scandium trifluoromethanesulfonate. The prepared gel polymer electrolyte has excellent magnesium anode compatibility, exhibits extremely low overpotential and highly reversible magnesium deposition-dissolution behavior, maintains a coulombic efficiency of ~98% after 600 cycles, and the overpotential of the symmetrical battery remains almost unchanged after 1000 cycles, which is less than 100 mV. The anodic oxidation decomposition potential is 2.5 V vs. Mg / Mg on stainless steel. 2+ In addition, by adding aluminum chloride to modify the electrolyte, the resulting gel electrolyte has a good match with the Mo6S8 positive electrode, and after 600 cycles at a rate of 0.5C, the average discharge capacity is 95.6mAh / g, the capacity retention rate is more than 88%, and the coulombic efficiency is close to 100%. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a digital photo of the gel polymer electrolyte obtained in Example 1 of the present invention after ring-opening polymerization of dibenzylamine magnesium chloride lithium chloride complex / tetrahydrofuran+1,3-dioxolane+initiator;
[0029] Figure 2 is the magnesium deposition-dissolution efficiency of the gel polymer electrolyte obtained in Example 2 on stainless steel, and the inset is the corresponding partial magnesium deposition-dissolution curve (the first ten cycles);
[0030] Figure 3 is the charge-discharge curve of the magnesium-to-magnesium symmetric battery of the gel polymer electrolyte obtained in Example 3, and the inset is the corresponding locally enlarged charge-discharge curve;
[0031] Figure 4 is the cyclic voltammetry curve of the gel polymer electrolyte obtained in Example 4 on stainless steel;
[0032] Figure 5 is the linear sweep voltammetric curve of the gel polymer electrolyte obtained in Example 5 on stainless steel;
[0033] Figure 6 It is the magnesium deposition-dissolution efficiency of the gel electrolyte obtained in Example 6 after ring-opening polymerization of dibenzylamine magnesium chloride lithium chloride complex + aluminum chloride (molar ratio of 1:2) / tetrahydrofuran + 1,3-dioxolane + initiator on stainless steel, and the inset is the corresponding partial magnesium deposition-dissolution curve (the first ten cycles);
[0034] Figure 7 is the charge and discharge cycle performance of the full battery obtained in Example 7 at a rate of 0.5C;
[0035] Figure 8 This is a digital photo of the 0.5 mol / L dibenzylamine magnesium chloride lithium chloride complex / tetrahydrofuran liquid electrolyte obtained in Comparative Example 1;
[0036] Fig. 9 It is the magnesium deposition-dissolution efficiency of 0.5 mol / L dibenzylamine magnesium chloride lithium chloride complex / tetrahydrofuran liquid electrolyte on stainless steel obtained in Comparative Example 2, and the inset is the corresponding partial magnesium deposition-dissolution curve (the first ten cycles);
[0037] Fig.10 This is the cyclic voltammetry curve of 0.5 mol / L dibenzylamine magnesium chloride lithium chloride complex / tetrahydrofuran liquid electrolyte on stainless steel obtained in Comparative Example 3;
[0038] Fig.11It is the magnesium deposition-dissolution efficiency of 0.5 mol / L dibenzylamine magnesium chloride lithium chloride complex / tetrahydrofuran + aluminum chloride (molar ratio of 1:2) liquid electrolyte on stainless steel obtained in Comparative Example 4, and the inset is the corresponding partial magnesium deposition-dissolution curve (the first ten cycles). DETAILED DESCRIPTION
[0039] The following describes several preferred embodiments of the present invention with reference to the drawings in the specification, so that the technical content is clearer and easier to understand. The present invention can be embodied in many different forms of embodiments, and the protection scope of the present invention is not limited to the embodiments mentioned in the text.
[0040] Example 1
[0041] A certain amount of 1,3-dioxolane was taken with a pipette, and then 3-4 wt % of scandium trifluoromethanesulfonate relative to the mass of 1,3-dioxolane was weighed and added thereto, and the mixture was mixed and stirred at 40° C. for 8-9 minutes to obtain a solution A.
[0042] Subsequently, according to the amount of 1,3-dioxolane, 3 volumes of dibenzylamine magnesium chloride lithium chloride complex / tetrahydrofuran electrolyte were pipetted with a pipette and added to solution A (i.e., the volume ratio of 1,3-dioxolane to dibenzylamine magnesium chloride lithium chloride complex / tetrahydrofuran electrolyte was 1:3), and vigorously stirred at room temperature (stirring speed was about 1000 r / min) until a homogeneous solution was obtained to obtain precursor solution B.
[0043] The precursor solution B was allowed to stand at room temperature for 24 hours to obtain a gel polymer electrolyte.
[0044] The above operations were all carried out in a glove box filled with argon atmosphere (water content <0.01 ppm, oxygen content <0.01 ppm).
[0045] Figure 1 This is a digital photo of the precursor solution B after it was left standing at room temperature for 24 hours. It can be seen that the resulting gel electrolyte is reddish brown and transparent and has no fluidity. Even if the black-cap bottle is turned upside down, the electrolyte still remains at the bottom of the bottle and does not flow down.
[0046] Example 2
[0047] According to Example 1, the precursor solution B was prepared, and a 2032 type 316 stainless steel battery shell was used as the positive electrode. A certain amount of the precursor solution B was added, metal magnesium was used as the negative electrode, and a polyethylene film was used as a separator. The button cells were assembled and the magnesium deposition-dissolution performance test was performed.
[0048] The above operations were all carried out in a glove box filled with argon atmosphere (water content <0.01 ppm, oxygen content <0.01 ppm).
[0049] Subsequently, the button cell was left to stand for 24 hours and then subjected to charge and discharge cycles with a charge and discharge current of 0.1 mA cm -2 , discharge for 30 minutes, and the charge cut-off voltage is 1.0V. Magnesium deposition-dissolution efficiency is as follows Figure 2 As shown, the inset is the corresponding deposition-dissolution curve. The deposition-dissolution overpotential of the obtained gel electrolyte on stainless steel is about 0.1V. There is an activation process in the early stage of the cycle. The magnesium deposition-dissolution efficiency gradually increases from 70% and finally stabilizes at about 98.5%. After 600 cycles, the average coulomb efficiency is about 98%, and it shows good cycle stability.
[0050] Example 3
[0051] According to Example 1, the precursor solution B was prepared, and metal magnesium was used as the positive electrode. A certain amount of the precursor solution B was added, metal magnesium was used as the negative electrode, and a polyethylene film was used as the separator to assemble into a symmetrical button cell.
[0052] The above operations were all carried out in a glove box filled with argon atmosphere (water content <0.01 ppm, oxygen content <0.01 ppm).
[0053] Subsequently, the symmetrical button cell was left to stand for 24 hours and then subjected to charge and discharge cycles with a charge and discharge current of 0.1 mA cm -2 The charge and discharge time is 30 minutes. The charge and discharge curve of the symmetrical battery is as follows Figure 3 As shown, it can be seen that the overpotential in the early stage of the cycle is about 0.12V, and after 1200 hours of charge and discharge cycles, the overpotential is about 0.1V, which may be attributed to the short activation process in the early stage. Overall, after 1500 hours of charge and discharge cycles, the overpotential of the installed symmetrical battery has no obvious increase and has been maintained at about 0.1V, which fully proves the good magnesium anode compatibility and excellent cycle stability of the gel electrolyte.
[0054] Example 4
[0055] According to Example 1, the precursor solution B was prepared, and a 2032 type 316 stainless steel battery shell was used as the positive electrode. A certain amount of the precursor solution was added, metal magnesium was used as the negative electrode, and a polyethylene film was used as a separator. The button battery was assembled and then left to stand for 24 hours.
[0056] The above operations were all carried out in a glove box filled with argon atmosphere (water content <0.01 ppm, oxygen content <0.01 ppm).
[0057] Subsequently, the assembled button cell was subjected to cyclic voltammetry test outside the glove box with a scan rate of 1 mV s -1 , the voltage range is -1~2V. The cyclic voltammetry test results are as follows Figure 4As shown, it can be seen that at -0.26V vs.Mg / Mg 2+ Magnesium deposition begins to occur at 0.6V vs.Mg / Mg 2+ The oxidation peaks on the left and right correspond to the dissolution of magnesium, and the peak current density is about 2.0 mA cm -2 Compared with the liquid electrolyte in Comparative Example 1, the polarization during magnesium deposition-dissolution is lower, which is mainly due to the formation of a more stable solid electrolyte interface (SEI). However, the obtained gel electrolyte exhibits a lower peak current value, which may be due to the lower conductivity of the gel electrolyte than the liquid electrolyte.
[0058] Example 5
[0059] According to Example 1, the precursor solution B was prepared, and a 2032 type 316 stainless steel battery shell was used as the positive electrode. A certain amount of the precursor solution was added, metal magnesium was used as the negative electrode, and a polyethylene film was used as a separator. The button battery was assembled and then left to stand for 24 hours.
[0060] The above operations were all carried out in a glove box filled with argon atmosphere (water content <0.01 ppm, oxygen content <0.01 ppm).
[0061] Subsequently, the assembled battery was subjected to a linear voltammetric sweep test outside the glove box at a sweep rate of 5 mV s -1 The linear voltammetric scan results are as follows: Figure 5 As shown in Figure 2, the anodic oxidation potential of the obtained gel electrolyte on stainless steel reaches 2.5 V vs. Mg / Mg 2+ above.
[0062] Example 6
[0063] Weigh a certain amount of aluminum chloride, slowly add it to tetrahydrofuran, place it in a magnetic stirrer and stir it thoroughly to dissolve, and prepare a 1.0mol / L aluminum chloride solution. Then slowly drip 1.0mol / L of dibenzylamine magnesium chloride lithium chloride complex electrolyte in proportion, continue stirring for 24 hours, and obtain a dibenzylamine magnesium chloride lithium chloride complex + aluminum chloride (molar ratio of 1:2) / tetrahydrofuran electrolyte with a magnesium ion concentration of 0.5mol / L. All of the above operations are carried out in a glove box filled with argon atmosphere (water content <0.01ppm, oxygen content <0.01ppm).
[0064] A certain amount of 1,3-dioxolane was pipetted with a pipette, and then 3-4 wt% of scandium trifluoromethanesulfonate relative to the mass of 1,3-dioxolane was weighed and added thereto, and the mixture was mixed and stirred at 40°C for 8-9 minutes to obtain solution A. Subsequently, 3 times the volume of 0.5 mol / L dibenzylamine magnesium chloride lithium chloride complex + aluminum chloride (molar ratio of 1:2) / tetrahydrofuran electrolyte was pipetted with a pipette according to the amount of 1,3-dioxolane and added to solution A (i.e., the volume ratio of 1,3-dioxolane to dibenzylamine magnesium chloride lithium chloride complex + aluminum chloride / tetrahydrofuran electrolyte was 1:3), and the mixture was vigorously stirred at room temperature (stirring speed of about 1000 r / min) until a homogeneous solution was obtained to obtain precursor solution B.
[0065] A 2032 type 316 stainless steel battery shell was used as the positive electrode, a certain amount of the above-mentioned precursor solution B was added, metal magnesium was used as the negative electrode, and a polyethylene film was used as the separator to assemble a button cell. The above operations were all carried out in a glove box filled with argon atmosphere (water content <0.01ppm, oxygen content <0.01ppm).
[0066] After the assembled battery was left to stand for 24 hours, the magnesium deposition-dissolution test was performed with a discharge time of 30 minutes, a charge cut-off voltage of 1.0 V, and a current density of 0.1 mA cm -1 , the results are as follows Figure 6 As shown, the initial coulombic efficiency is 86%, the magnesium deposition-dissolution efficiency after stabilization reaches more than 98%, the average coulombic efficiency is as high as 97.8% after 160 cycles, and the dissolution overpotential is less than 60mV.
[0067] Example 7
[0068] According to the preparation of precursor solution C in Example 6, the deintercalation type Mo6S8 material was used as the positive electrode, a certain amount of precursor solution C was added, metal magnesium was used as the negative electrode, and a polyethylene film was used as a separator. The button cell was assembled and then left to stand for 24 hours.
[0069] The above operations were all carried out in a glove box filled with argon atmosphere (water content <0.01 ppm, oxygen content <0.01 ppm).
[0070] Subsequently, the assembled full battery was subjected to charge and discharge cycle testing in an electrochemical test system, with a cycle rate of 0.5C, a charge cutoff voltage of 2V, and a discharge cutoff voltage of 0.2V. Figure 7 As shown, the initial discharge capacity of the obtained full battery is 104 mAh / g, and the discharge capacity remains above 92 mAh / g after 600 cycles, the capacity retention rate reaches above 88%, and the coulombic efficiency remains at 100%. This shows that the obtained gel electrolyte has good positive electrode compatibility and also exhibits excellent cycle stability in the full battery.
[0071] Comparative Example 1
[0072] A certain amount of 1 mol / L dibenzylamine magnesium chloride lithium chloride complex / tetrahydrofuran electrolyte was taken with a pipette, and then the same volume of tetrahydrofuran solvent was added, and the mixture was stirred on a magnetic stirring table for 8 hours to obtain a 0.5 mol / L dibenzylamine magnesium chloride lithium chloride complex / tetrahydrofuran liquid electrolyte. The above operations were all performed in a glove box filled with argon atmosphere (water content <0.01 ppm, oxygen content <0.01 ppm). Figure 8 This is a digital photo of the liquid electrolyte. In sharp contrast to Example 1, when the black-cap bottle is inverted, the liquid electrolyte is not fixed at the bottom of the bottle, but flows to one end of the bottle cap due to gravity.
[0073] Comparative Example 2
[0074] According to Comparative Example 1, a 0.5 mol / L dibenzylamine magnesium chloride lithium chloride complex / tetrahydrofuran liquid electrolyte was prepared. Then, a 2032 type 316 stainless steel battery shell was used as the positive electrode, a certain amount of the above liquid electrolyte was added, metal magnesium was used as the negative electrode, and a polyethylene film was used as a diaphragm to assemble a button cell. The above operations were all carried out in a glove box filled with argon atmosphere (water content <0.01 ppm, oxygen content <0.01 ppm).
[0075] After standing for 4 h, the magnesium deposition-dissolution test was carried out in the electrochemical test system with a discharge time of 30 min, a charge cut-off voltage of 1.0 V, and a current density of 0.1 mA cm -1 , the results are as follows Fig. 9 As shown, the initial Coulomb efficiency is 68.8%, the efficiency after 5 cycles is 92%, the average efficiency of magnesium deposition-stripping after 1000 cycles is 98.3%, and the overpotential is about 100 mV.
[0076] Comparative Example 3
[0077] According to Comparative Example 1, a 0.5 mol / L dibenzylamine magnesium chloride lithium chloride complex / tetrahydrofuran liquid electrolyte was prepared. Then, a 2032 type 316 stainless steel battery shell was used as the positive electrode, a certain amount of the above liquid electrolyte was added, metal magnesium was used as the negative electrode, and a polyethylene film was used as a diaphragm to assemble a button cell. The above operations were all carried out in a glove box filled with argon atmosphere (water content <0.01 ppm, oxygen content <0.01 ppm).
[0078] After standing for 4 h, cyclic voltammetry was performed with a scan rate of 1 mV s -1 , the voltage range is -1~2V. The cyclic voltammetry test results are as follows Fig.10 As shown, it can be seen that at -0.26Vvs.Mg / Mg 2+Magnesium deposition begins to occur at 0.87V vs.Mg / Mg 2+ The oxidation peaks appearing on the left and right correspond to the dissolution of magnesium, and the peak current density is about 6.0 mA cm -2 ,Compared with the gel electrolyte, the polarization during the magnesium deposition-stripping process is larger, but the corresponding peak current value is also larger, which is mainly due to the inherent advantages of liquid electrolytes in conductivity.
[0079] Comparative Example 4
[0080] Weigh a certain amount of aluminum chloride, slowly add it to tetrahydrofuran, place it in a magnetic stirrer and stir it thoroughly to dissolve it, and prepare a 1.0 mol / L aluminum chloride solution. Then slowly drop 1.0 mol / L dibenzylamine magnesium chloride lithium chloride complex electrolyte in proportion, continue stirring for 24 hours, and obtain dibenzylamine magnesium chloride lithium chloride complex + aluminum chloride (molar ratio of 1:2) / tetrahydrofuran electrolyte with a magnesium ion concentration of 0.5 mol / L.
[0081] A 2032 type 316 stainless steel battery shell was used as the positive electrode, a certain amount of the above electrolyte was added, metal magnesium was used as the negative electrode, and a polyethylene film was used as the diaphragm to assemble a button cell. The above operations were all carried out in a glove box filled with argon atmosphere (water content <0.01ppm, oxygen content <0.01ppm).
[0082] After standing for 4 hours, the magnesium deposition-dissolution test was carried out with a discharge time of 30 minutes, a charge cut-off voltage of 1.0 V, and a current density of 0.1 mA cm -1 , the results are as follows Fig.11 As shown, the initial coulombic efficiency is 88.4%, the average efficiency of magnesium deposition-stripping after 350 cycles is 98.9%, and the overpotential is about 90 mV.
[0083] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. An application of a gel electrolyte in a rechargeable magnesium battery, the gel electrolyte comprising a magnesium salt, a ring-opening polymerization monomer, a solvent and an initiator, wherein the ring-opening polymerization monomer is 1,3-dioxolane.
2. The use according to claim 1, wherein: The magnesium salt is dibenzylamine magnesium chloride-lithium chloride complex or other magnesium chloride-lithium chloride complex.
3. The use according to claim 1, wherein: The solvent is tetrahydrofuran.
4. The use according to claim 1, wherein: The initiator is scandium trifluoromethanesulfonate, and the mass fraction of the initiator relative to 1,3-dioxolane is 3-4wt%.
5. The use according to claim 1, wherein: The magnesium ion concentration in the magnesium salt / tetrahydrofuran electrolyte is 0.5 mol / L.
6. The use according to claim 1, wherein: The volume ratio of the magnesium salt / tetrahydrofuran electrolyte to the ring-opening polymerization monomer is 3:
1.
7. The use according to claim 1, wherein: The gel electrolyte is prepared by the following method: Step 1), adding the initiator to the ring-opening polymerization monomer, and mixing at 40° C. for 8-9 minutes to obtain solution A; Step 2), adding magnesium salt / tetrahydrofuran electrolyte to the solution A, and vigorously stirring at room temperature until the solution is homogeneous, which is the precursor solution B; Step 3), leaving the precursor solution B at room temperature for more than 24 hours to obtain a transparent gel electrolyte.
8. The use according to claim 7, wherein: The method also includes first adding aluminum chloride to the magnesium salt / tetrahydrofuran electrolyte and reacting for 24 hours.
9. The use according to claim 7 or 8, wherein: The rechargeable magnesium battery is prepared by the following method: A 2032 type 316 stainless steel battery shell, metal magnesium, and deintercalation type Mo6S8 were used as the positive electrode, the precursor solution B was added, metal magnesium was used as the negative electrode, and a polyethylene film was used as a separator to assemble a button battery, which was left to stand for more than 24 hours.
10. The use according to claim 9, wherein: The rechargeable magnesium battery is cycled 600 times at room temperature, and the average discharge specific capacity is 95.6 mAh / g at a rate of 0.5C. After 600 charge and discharge cycles, the discharge specific capacity remains above 92 mAh / g, and the capacity retention rate reaches above 88%.
Citation Information
Patent Citations
Electrochemical device with a magnesium anode and a stable, safe electrolyte compatible with sulfur
CN103534862A
In-situ preparation and application of polymer solid electrolyte
CN114430064A
Bisamide-based electrolyte for magnesium battery
EP2824751A1
Electrochemical device with a magnesium anode and a stable, safe electrolyte compatible with sulfur
US20120107698A1
Rechargeable high temperature electrochemical battery
US4054729A